Download presentation

Presentation is loading. Please wait.

Published byJocelin Simpson Modified over 8 years ago

1
9.2 – Adding & Subtracting Rational Expressions

2
Remember adding & subtracting fractions?

3
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator!

4
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4

5
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 4 3

6
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 4 3

7
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 4 3 4 3 12

8
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 4 3 4 3 12 12

9
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 = 4 3 4 3 12 12

10
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 = _ 1 4 3 4 3 12 12 12

11
9.2 – Adding & Subtracting Rational Expressions Remember adding & subtracting fractions? –Have to get a common denominator! 2 _ 3 3 4 4. 2 _ 3. 3 = 8 _ 9 = _ 1 4 3 4 3 12 12 12 –Same w/rational expressions!

12
Ex. 1 Simplify each expression

13
a. 6 + 8 ab a

14
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + ab a ab

15
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b)

16
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab

17
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab

18
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a(b) = 6 + 8b ab ab = 6 + 8b ab

19
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6

20
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m

21
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m (m+2)(m-2)

22
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2)

23
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2)

24
Ex. 1 Simplify each expression a. 6 + 8 ab a 6 + 8 = 6 + 8(b) ab a ab a (b) = 6 + 8b ab ab = 6 + 8b ab b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m 3(m+2)(m-2)

25
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2)

26
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2)

27
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2)

28
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2)

29
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4

30
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 3(m+2)(m–2)

31
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 = m + 4 3(m+2)(m–2)

32
Ex. 1 Simplify each expression b. m _ 2 m 2 – 4 3m + 6 m _ 2 (m+2)(m-2) 3(m + 2) 3m _ 2 (m – 2) 3(m+2)(m-2) 3m – 2(m – 2) 3(m + 2)(m – 2) 3m – 2m + 4 = m + 4 _ 3(m+2)(m–2)

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google